Exploiting the effect of PEO parameters on the surface of AISI 1020 low-carbon steel treated in a TaOH-rich electrolyte - Marcuz, N.; Ribeiro, R. P. [UNESP]; Rangel, E. C. [UNESP]; Cruz, N. C. [UNESP]; Possato, L. G. [UNESP]; Coan, K. S. [UNESP]; Grandini, C. R. [UNESP]; Correa, D. R.N. [UNESP] (Elsevier, 2024)
This study used PEO treatment and a TaOH-rich electrolyte to coat AISI 1020 low-carbon steel to enhance its anti-corrosion and wear properties, targeting its usage as a medical device. The effect of time, duty cycle, frequency, and Ta(OH)5 concentration on the chemical and phase composition, topography, wettability, and roughness of the obtained coatings were addressed. The results indicated that the Fe-based oxide coatings had a rough and super-hydrophilic surface. The phase composition of the coatings was formed mainly of Ta2O5, hematite (Fe2O3), and a minor amount of rust (Fe(OH)2), with the chemical analyses also indicating the presence of some absorbed molecules. Once the best PEO parameters were established (200 V, 5 min, 60 %, 1000 Hz, and 40 g/L Ta(OH)5), the previous mechanical, corrosion, and wear tests evidenced the positive effect of the chemical species deposited in the surface when compared to the substrate. In this way, PEO treatment applied on AISI 1020 low-carbon steel in a TaOH-rich electrolyte can be an adequate alternative to produce low-cost materials for medical devices, especially as a potential substitute for stainless steel and titanium-based alloys in surgical instruments.
Keywords: Corrosion; Low-carbon steel; Medical device; PEO; Ta oxide; Wear